Analysis of Meaning in Song Lyrics "I'd Like to Watch You Sleeping"By Sal Priadi - Khairunissa Nugroho; Nadif Yulkham; Gracia Maketake; Sarah Lyimo (Jurnal Sastra Indonesia, 2025)
The development of contemporary Indonesian music gave rise to a complex, metaphorical lyric style, demanding a deep understanding to uncover the hidden meaning behind the songwriter's language play. Semiotic analysis is an essential approach for dissecting the relationships between markers to bridge the gap in understanding between music creators and connoisseurs. This research has a dual purpose: to identify and analyze the representation of denotative and connotative meanings in the lyrics of the song "I'd Like to Watch You Sleeping" by Sal Priadi, and to describe the unity of meaning the author seeks to convey through language symbols. The method used is a qualitative descriptive approach with content analysis, involving the systematic processes of reading, listening, taking notes, and analyzing textual data in the form of song lyrics and audio recordings. The results showed the use of absurd and metaphorical markers such as "more often gaping", "cartoon characters on television", "the body evaporates into rain", and "playing in the clouds" which convey signs in the form of deep admiration, hope for eternity, transformation of love, and the desire to become an integral part of a lover. These findings reveal patterns of symbolic language use in contemporary song lyrics and provide insight into the construction of connotative meanings through deviations from denotative meanings. This research is expected to serve as a reference for the study of linguistics and literature and to make a practical contribution to the appreciation of contemporary Indonesian music.